2012
DOI: 10.1128/jb.01494-12
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Bioinformatic Analyses Implicate the Treponema pallidum Tp34 Lipoprotein (Tp0971) in Transition Metal Homeostasis

Abstract: Metal ion homeostasis is a critical function of many integral and peripheral membrane proteins. The genome of the etiologic agent of syphilis, Treponema pallidum, is compact and devoid of many metabolic enzyme genes. Nevertheless, it harbors genes coding for homologs of several enzymes that typically require either iron or zinc. The product of the tp0971 gene of T. pallidum, designated Tp34, is a periplasmic lipoprotein that is thought to be tethered to the inner membrane of this organism. T ransition metal io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Both calorimetric [26] and hydrodynamic means [26,32,33] have demonstrated that the Treponema pallidum protein Tp34 interacts with the human mucosal iron-sequestering protein hLF in a 2:1 ratio. In determining the proper model to employ in the analyses of Tp34/hLF data, it is instructive to examine the respective crystal structures of the proteins (a co-crystal structure of the proteins has not been determined).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both calorimetric [26] and hydrodynamic means [26,32,33] have demonstrated that the Treponema pallidum protein Tp34 interacts with the human mucosal iron-sequestering protein hLF in a 2:1 ratio. In determining the proper model to employ in the analyses of Tp34/hLF data, it is instructive to examine the respective crystal structures of the proteins (a co-crystal structure of the proteins has not been determined).…”
Section: Resultsmentioning
confidence: 99%
“…20 kDa), which is far smaller than hLF, is dominated by an eight-stranded β-sandwich that is similar to the classic Ig-fold [26]. Both hLF and Tp34 are monomeric in solution in the absence of metal ions, but the presence of divalent cations of the transition metals induces the dimerization of Tp34 [26,32]. Because the current studies were performed in the absence of any added metal ions, it was assumed that only the monomeric forms of the proteins were present.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations